The Cyclicality of Sales, Regular and Effective Prices : Business Cycle and Policy Implications - Coibion, Olivier (IMF Working Papers; Working Paper ;, 2012)
We study the cyclical properties of sales, regular price changes and average prices paid by consumers ("effective" prices) in a dataset containing prices and quantities sold for numerous retailers across a variety of U.S. metropolitan areas. Both the frequency and size of sales fall when local unemployment rates rise and yet the inflation rate for effective prices paid by consumers declines significantly with higher unemployment. This discrepancy can be reconciled by consumers reallocating their expenditures across retailers, a feature of the data which we document and quantify. We propose a simple model with household shopping effort and store-switching consistent with these stylized facts and document its implications for business cycles and policymakers.